Key Technology of Three-dimensional Combined Wave Dissipation and Its Application in Seawall Engineering - ZHAN Damei; GONG Chunjuan (Renmin Zhujiang)
In order to optimize the technology for seawalls to resist wave damage more scientifically and aesthetically,and to enhance the ecological and landscape functions of the seawalls,a optimized combination technology of wave-dissipation and wave-resistance bodies such as concrete accropode blocks,concrete hollow square blocks,reinforced concrete fence boards,and reverse crown walls is developed,which takes into account the size of the waves and the characteristics of the motion trajectory,and sets up different wave-dissipation blocks at different positions on the slope,and makes full use of the characteristics of each wave-dissipation block to improve the economy and safety of seawall structure,and achieve better engineering application effect.In addition,the three-dimensional combined wave dissipation system proposed is verified through application cases,which not only ensures the shoreline landscape effect,but also has good wave dissipation effect.Therefore,it is of high practical value and useful reference for similar projects.